Democracia, meio ambiente e a (des)motivação para participar: uma etnografia da (des)motivação para participação política ambiental em São Carlos/SP - Gomes, Heitor Menezes (Universidade Federal de São Carlos, 2024)
Cities are public spaces where differences coexist. Therefore, the right to urban public space constitutes a right to citizenship, encompassing all those who live or wish to live in cities. Political participation, to consolidate this right, occurs within a democratic framework, which extends itself beyond voting for representatives of the people's will. Citizenship within democracy also stems from people's ability to organize themselves to exert influence on the organization of their space. In São Carlos (SP), the Fórum de Cidadãos Participantes is a recent grassroots movement that, in partnership with the Public Ministry and the Center for Studies in Environmental Democracy, aims to address local environmental conflicts participatively, empowering members for political action. With this in mind, the research sought to understand the structure, relationships, forms of action, and effects of the activities of the Fórum de Cidadãos Participantes on in-person and virtual involvement of members, aiming to enhance participation. For this purpose, participant observation methodology was employed, whereby the researcher accompanied the group as a member for a period of four months, attending nine in-person activities. Data collection was done through field notes. As a result, 29 motivating and demotivating factors were identified and analyzed, with 19 considered motivating and 10 demotivating. The factors were organized into three categories: Sociability, Organizational, and Political, within the Motivating and Demotivating classes. The analyzed factors strongly converge with the literature, having been identified in various participatory organizations and movements. Through these analyses, it was possible to suggest a sequence of six steps to strengthen motivating factors and mitigate the occurrence of demotivating ones.
Democracy, environment and (des)motivation to participate: an etnography of (des)motivation to environmental political participation in São Carlos/SP
Keywords: Participação social; Participação observante; Políticas públicas; Motivação; Conflitos ambientais; Social participation; Participant observation; Policies; Motivation; Environmental conflicts; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL